Higher education in Southeast Asia : blurring borders, changing balance - Welch, Anthony R. (Abingdon, Oxon : Routledge, 2011)
'This is the first book to systematically chart and comparatively assess the trend towards private higher education in Southeast Asia. It includes a substantial analysis of key policy issues, as well as detailed case studies of Indonesia, Malaysia, Thailand, Philippines, and Vietnam'--Provided by publisher.
'Throughout SouthEast Asia, the balance between public and private higher education is changing. Caught between conflicting imperatives, of spiralling demand, and limited resources, the balance between public and private higher education systems in South East, South, and East Asia has shifted markedly. Twenty years ago, no private universities existed in Malaysia, or Viet Nam - now private higher education is challenging for a major role. But this is not the whole story. The same cost pressures affect public HEIs. Governments press for more enrolments, but state support is slipping, at least in per-student terms. The effects push public HEIs to diversify income sources, by various means: offering high demand courses for high fees, or developing parallel courses, taught at nights or weekends, sometimes in shopping malls, for high fees. Is there a connection between the two trends? What is argued is that we are witnessing not merely a changing balance between public and private sectors, but a blurring of borders between them, with public HEIs now often behaving more like private, for-profit institutions. The book charts and illustrates these trends, posing questions about their meaning, including issues of transparency, equity, and what the reforms might mean for traditional conceptions of public good in higher education'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Private universities and colleges -- Southeast Asia; Education, Higher -- Southeast Asia; Education and state -- Southeast Asia